Minat Masyarakat dalam Proses Pembuatan Noken Sebagai Nilai Budaya Pada Suku Miyah Kabupaten Tambrauw - Nikmatul Ula, Siti Nurul; Nurhidaya, Nurhidaya; Purwanti, Nanik; Sedik, Yubelina Gema (Jurnal Noken: Ilmu-Ilmu Sosial, 2023)
Noken is a typical Papuan knitted bag, which cannot be separated from people's daily lives. In particular, the Miyah tribe in the Tambrauw district area, in making noken, they use raw materials from the bark fiber of the ganemon tree and only women can make noken, because they consider that a woman who cannot make noken is not yet mature and worthy of marriage, and likewise on the contrary. The method used in this research is descriptive qualitative, namely by describing the entire series of research from the data search stage, data analysis and drawing conclusions. So the results obtained are that the interest of the people in Tambrauw Regency, especially the Miyah Tribe, in making noken art crafts is still lacking, this is due to the obstacles that occur, namely the lack of socialization from the local government, the availability of raw materials which is still difficult, plus the pandemic so that marketing is not optimal. . Therefore, efforts are made to provide good facilities and infrastructure as well as providing training and guidance, both in improving the community's creative economy and maintaining the preservation of the noken culture itself.